Review Of Good Faith And Honesty (Goodfaith And Fair Dealing) In Business Contracts Based On Indonesia Legal Principles And International Law In Legal Reform National Contract - N. Ike Kusmiati (Kurdish Studies, 2024)
The implementation of good faith in civil law and common law systems, including Indonesia and other ASEAN countries, still leaves a phenomenon in society where violations still occur.in practice, even though according to the teachings of natural law, doing good is a command of the creator, because According to reason, humans must act in good faith. The research method used in this research is descriptive analytical, describing the facts and primary, secondary and tertiary legal materials, namely statutory regulations, international conventions, both CISG and UNIDROIT, the approach used is normative juridical through grammatical, authentic and systematic interpretation as well as legal construction relating to the object researched. With a comparative approach between countries in civil law and common law systems especially ASEAN countries. Field research was carried out through interviews. Technique Data collection was carried out by document study, related to good faith. Data analysis in this research is qualitative juridical. The research results show that implementation is good faith and honesty in business contracts based on the principles of Indonesian law and international law have not been implemented, it is proven that a civil case has been brought to court on the basis of breach of contract and/or acts of contravention law. According to natural law, doing good is commanded by the Creator. Efforts of each country does not provide limitations to this principle, it is reasonable, because it is transcendental/metaphysical in nature. Study results compared with ASEAN countries, both civil law systems and common law systems, this principle interpreted as not conflicting with the law, good morals, customs, equality, voluntarism, good will, cooperation, honesty, fairness and justice. Meanwhile in Indonesia it means propriety, honesty, no harm, no violation of other people's rights. As a concept of good faith in implementation of a business contract, the parties act on the basis of good faith having three ideas, important, namely the obligation of the parties to cooperate according to the objectives of the contract, compliance with standards of behavior honesty, compliance with reasonable behavior in the interests of the parties. It is a moral obligation from humans to carry out promises. Regarding the renewal of national contract law, BPHN carried out amendments to Book III of the Civil Code, Part 2 concerning obligations arising from agreements, can accommodate modern contracts in both CISG and UNIDROIT.